Development module of scrutinization and report generator for web-based ARCA system / Mohd Fahmy Izwan Zulkhafri - Zulkhafri, Mohd Fahmy Izwan (2020)
The manual method of taking student attendance activity is not effective because there are several challenges to that kind of method. The data collected through the conventional method is difficult to manage: time-consuming to be scrutinized, and it causes the wastage of human and material resources. Therefore, the aim of this project is to develop a module of scrutinization of college application in UiTM Perlis and also module report generator to be integrated with existing system of ARCA system. This report generator module will retrieve the data from the database and will save as the PDF format. The study involved three main phases which are requirement identification phase, design and development phase, and testing phases in part of the research methodology. The study also involves usability and functionality testing by using unit test, script testing and distributed post-task questionnaires respectively to the college manager, college staff, staff resident college and also to the students in UiTM Perlis branch, Campus Arau. The results of usability testing show all of the users have been agree with ARCA system that very usefulness to use as their day-to-day work and also very satisfy with the ARCA system. In short, this project is conducted to find the feasible solution for the related issues by implementing this module for the research and development purpose.